Energy harvesting using two-dimensional (2D) d-silicates from abundant natural minerals. Issue 6 (30th January 2023) - Mahapatra, Preeti Lata; Singh, Appu Kumar; Tromer, Raphael; R., Karthik; M., Ambresha; Costin, Gelu; Lahiri, Basudev; Kundu, Tarun Kumar; Ajayan, P. M.; Altman, Eric I.; Galvao, Douglas S.; Tiwary, Chandra Sekhar
Abstract : This paper demonstrates the exfoliation of naturally occurring silicates into two-dimensional structures. Moving the d-silicate device repeatedly in a vertical direction causes it to react robotically and generate up to ∼400 mV of voltage. Abstract : In the last decade, the materials community has been exploring new 2D materials (graphene, metallene, TMDs, TMCs, MXene, among others) that have unique physical and chemical properties. Recent research has suggested a new family of 2D materials known as 2D silicates. They are predicted to exhibit exciting properties (such as high catalytic activity, piezoelectricity, and 2D magnetism). In the current work, we demonstrate a generic approach to the synthesis of large-scale 2D silicates from selected minerals, such as Diopside (d). Different experimental techniques were used to confirm the existence of the 2D structures (named 2D-d-silicates). Insight into the structural characteristics and energy harvesting systems (flexoelectric response generating voltage up to 10 V) was also obtained by DFT simulations. The current method is entirely generic and can be used for the elusive large-scale synthesis of 2D silicates and their derivatives.